Analisis Pengaruh Kebijakan Moneter dan Ekonomi Digital terhadap Stabilitas Nilai Tukar di Indonesia: Pendekatan Autoregressive Distributed Lag (ARDL) - Andien Ayu Ristina; Sitti Balqis Hamidah; Sindy Oktafia; Muhammad Yusuf Bahtiar (Indo Publishing, 2026)
This research examines the effects of digital economic development and monetary regulations on the resilience of the Indonesian rupiah exchange rate. The research uses an Autoregressive Distributed Lag (ARDL) approach to test the dynamic relationship between periods. The findings indicate that monetary policy instruments, such as interest rates, as well as growth in the digital economy, have a significant impact on exchange rate fluctuations. Although digitalization enhances transaction efficiency and expands access to global markets, it also creates more complex volatility in exchange rates. The study’s conclusion indicates that monetary policy and developments in the digital economy mutually influence exchange rates, so policymakers need to implement comprehensive strategies to maintain macroeconomic stability in the digital era.